Undetermined Ruptured Low‐Grade Appendiceal Mucinous Neoplasm Following High‐Energy Blunt Abdominal Trauma Requiring Emergency Laparotomy - Ippei Matsuo; Tetsuya Yumoto; Akari Tsuji; Ryo Tanabe; Toshihisa Matsumura; Mikoto Shimabara; Masaaki Akai; Shoji Takagi; Hiromichi Naito; Atsunori Nakao (Clinical Case Reports)
ABSTRACT Blunt abdominal trauma causing intraperitoneal injury and/or bleeding can be life‐threatening, requiring immediate intervention. Diagnosing these cases can be challenging, especially when pre‐existing conditions are involved. Low‐grade appendiceal mucinous neoplasm (LAMN) is a rare tumor of the appendix that can lead to pseudomyxoma peritonei. Herein, we present a case of ruptured LAMN following blunt abdominal trauma after a high‐energy head‐on collision, complicating the differentiation from other intraperitoneal injuries. A 42‐year‐old Japanese female was brought to our hospital following high‐energy head‐on collision. She presented with stable vital signs, complaining of anterior chest pain and abdominal tenderness without peritoneal irritation. Computed tomography scans indicated multiple fractures in her chest and complex fluid around the Douglas fossa extending to the ileocecal area, with a slightly dilated appendix tip. Despite stable vitals, emergency laparotomy was needed for suspected peritonitis and/or intraperitoneal hemorrhage. Emergency laparotomy revealed yellowish, jelly‐like ascites and a ruptured appendiceal tumor. LAMN was suspected, and the appendix was completely resected, with cytoreductive surgery carefully performed. Histopathological examination confirmed the diagnosis of LAMN. Postoperative course was uneventful, and the patient was discharged on Day 13 and referred for further LAMN management. This case report highlights the diagnostic difficulties of LAMN rupture following blunt abdominal trauma, stressing the need to consider rare conditions like LAMN in differential diagnoses of acute abdomen posttrauma.